Faktor Lingkungan dan Perilaku Masyarakat yang Berhubungan dengan Kejadian Filariasis di Kabupaten Sambas - Ardias, Ardias; Setiani, Onny; Darundiati, Yusniar Hanani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Filariasis is an endemic disease in Indonesia. Sambas district is declared endemic filariasis with Mfrate> 1%. The number of cases at this time amounted to 63 peoples, the highest cases in sub district Sejangkung with 24 cases and 14 cases in Sebawi district. Based on the preliminary survey conducted in May 2011, there were several factors that play a role in transmission of filariasis cases, among other environmental factors and behavior of people in the Sambas district. The research aimed to identify environmental factor and behavioral associated with the incidence of filariasis in Sambas district.Methods : This research was an observational research using a case control design, with 32 sample cases dan 32sample control. Sampling of the population of cases and controls performed by matching the age and sex and statusof microfilaria. Data collected through observation and interviews. Data were analyzed by using biavariate analyzes with chi-square and with multivariate logistic regression. Statistical analysis showed that of 8 (eight) variables were analyzed, there are 6 (six) variables are shown to be associated to the incidence of filariasis in Sambas district.Results : That is breeding place of mosquitoes (p-value:0,002, OR:38,031, 95%CI :3,737-387,045), the resting place of mosquitoes (p-value:0,006, OR:4,840; 95%CI :1,682-13,930), the use of wire netting (p-value: 0,013, OR: 27.201 95% CI: 2.026-365-1996), a habit out of the house (p-value: 0,009 OR : 39.054 ; 95% CI: 2.534-601.793), the use ofinsect repellent, (p-value: 0,007, OR: 27.213 95% CI: 2.520-293.853), the use of bed nets (p-value: 0,023, OR: 3, 735; 95% CI: 1,314–10,618).Conclusion of this study is environmental factors and poor people’s behavior was very influently to the incidence offilariasis, while the type of work and level of knowledge respondents did not affect with the incidence of filariasis inSambas district.Key words : Filariasis, Environmental Factor, Behaviour.